DIGITAL SPIRITUALITY: PELUANG SEKALIGUS TANTANGAN GEREJA KONTEMPORER - Imbran Batelemba Bonde (SIAP: Jurnal Teologi dan Pendidikan Kristen, 2021)
ABSTRACT This article is an initial investigation into the increasingly popular digitalspirituality. Taking Theovlogy, Ignite GKI, and Unicult as examples, thisarticle aims to show that the practice of spirituality is increasinglydeveloping and adapting. Simultaneously, it also reconsiders the termspirituality itself which cannot be taken in a narrow sense. In the end,digital spirituality is inevitable, the church must be ready and adaptable,as well as prepare a liturgy that is friendly in the public sphere. Keywords: Spirituality, online, chrurch, digital.